2018
DOI: 10.1103/physrevb.97.241410
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoplasmonic enhancement of Faraday rotation in patterned graphene metasurfaces

Abstract: Faraday rotation is a fundamental property present in all non-reciprocal optical elements. In the THz range, graphene displays strong Faraday rotation; unfortunately, it is limited to frequencies below the cyclotron resonance. Here we show experimentally that in specifically design metasurfaces, magneto-plasmons can be used to circumvent this limitation. We find excellent agreement between theory and experiment and provide new physical insights and predictions on these phenomena. Finally, we demonstrate strong… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…In 2018, Tamagnone et al experimentally demonstrated a graphene reflectarray metasurface for terahertz beam steering . Specifically, the reflective element consisted of Au antennas/graphene, a silicon spacer, and Ag/Al reflective film (see Figure a,b).…”
Section: Beam Steering Based On Electromagnetic Metasurfacesmentioning
confidence: 99%
“…In 2018, Tamagnone et al experimentally demonstrated a graphene reflectarray metasurface for terahertz beam steering . Specifically, the reflective element consisted of Au antennas/graphene, a silicon spacer, and Ag/Al reflective film (see Figure a,b).…”
Section: Beam Steering Based On Electromagnetic Metasurfacesmentioning
confidence: 99%
“…The degree of optical field confinement achieved λ IR /2d = 26.5, where d is the Si-ND diameter, is comparable, at the same wavelength, to the reduction of the plasmon wavelength in graphene. 30,31 This is also far better than what can be obtained using noble metals. As a matter of fact, a micron-scale gold stripe would be necessary to support a LSPR at the same energy, 32,33 leading to additional important thermal dissipation due to the long propagation length of the localized plasmon.…”
mentioning
confidence: 80%
“…The progress in the large area growth and transfer of SLG [ 23,31 ] has enabled the development of SLG‐based active devices such as modulators, [ 18 ] absorbers, [ 32 ] phase shifters, [ 5 ] and reflect‐arrays [ 33 ] at THz frequencies. [ 34–36 ] In all these devices, phase and amplitude control of the incident light were achieved by tuning the SLG charge density by all‐electronic [ 37,38 ] or all‐optical [ 39,40 ] architectures.…”
Section: Introductionmentioning
confidence: 99%
“…[17,19] For free standing SLG, higher σ results in higher reflection and lower transmission of THz-frequency light, and the absorption reaches its maximum when the sheet resistance (R s ) of SLG reaches half of the free space impedance (Z 0 = 377 Ω). [30] The progress in the large area growth and transfer of SLG [23,31] has enabled the development of SLG-based active devices such as modulators, [18] absorbers, [32] phase shifters, [5] and reflect-arrays [33] at THz frequencies. [34][35][36] In all these devices, phase and amplitude control of the incident light were achieved by tuning the SLG charge density by all-electronic [37,38] or all-optical [39,40] architectures.…”
mentioning
confidence: 99%